DETERMINING THE FOCAL MECHANISM OF AN EARTHQUAKE IN THE TRANSCARPATHIAN REGION OF UKRAINE - Malytskyi, D.; Muyla, O.; Pavlova, A.; Hrytsaj, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
In the paper, the theory of seismic wave propagation in anisotropic media is presented, with the use of the matrix method when determining the mechanisms of local earthquakes. These issues are of importance in seismic studies in the Carpathian region where the number of seismic stations is insufficient. The work is aimed at the development of a methodology for calculating displacements on the surface of anisotropic medium and determining the mechanisms of local earthquakes with the use of the graphic method. The purpose of the graphic method consists in making it possible to use seismic records at the stations with indistinct polarities of first P-wave motions. The ratio between the amplitudes of direct P- and S-waves is used as an auxiliary parameter. The research results are illustrated with examples of using the records of 04.04.2013 event near Nyzhnye Selyshche (φ=48,1977, λ=23,4663, h=1,73 km, ML=2). Comparative analysis is carried out of seismograms calculated with the matrix method and those recorded at a seismic station, which confirms the effectiveness of the methodology for determining the seismic source parameters. Based on the graphic method, spectral and geometric parameters of the seismic source have been obtained: seismic moment, radius of shear dislocation, slip area, mean fault slip, stress drop, energy and magnitude. Scientific novelty of the work consists in developing a method of calculating the displacement field in anisotropic media with the use of the matrix method and in amending the graphic method so as to ensure determining the mechanisms of local earthquakes in the Carpathian region where the number of seismic stations is limited. Practical application of the work is in determining the source parameters of local earthquakes, based on the developed approaches, which is of crucial importance in local seismological studies. The version of the matrix method developed in this work for calculating seismic wave propagation in anisotropic media can be used for determining the tensor of seismic moment with the number of seismic stations being limited.